Evolution of age at primiparity in pinnipeds in the absence of the quality–quantity trade‐off in reproduction. Issue 9 (15th April 2019) - Kalberer, Stephanie; DeRango, Eugene; Trillmich, Fritz; Krüger, Oliver
Abstract: Age at primiparity (AP) is a key life history trait which is crucial to the evolution of life history strategies. This trait is particularly interesting in pinnipeds (walrus, eared seals, and true seals), which are monotocous animals. Thus, the commonly observed trade‐off between offspring quality and quantity does not apply to this taxon. Therefore, comparative studies on the evolution of AP might shed light on other important evolutionary correlates when litter size is fixed. Using phylogenetic generalized least squares analyses, we found a strong negative and robust correlation between relative birth mass (mean pup birth mass as a proportion of mean adult female mass) and AP. Rather than trading‐off an early start of reproduction with light relative offspring mass, this result suggests that pinnipeds exhibit either faster (i.e., higher relative offspring mass leading to shorter lactation length, and thus shorter interbirth interval) or slower life histories and that an early AP and a heavy relative offspring mass co‐evolved into a comparatively fast life history strategy. On the other hand, AP was positively related to lactation length: A later start of reproduction was associated with a longer lactation length. Consequently, variation in AP in pinnipeds seems to be affected by an interplay between costs and benefits of early reproduction mediated by relative investment into the single offspring via relative birth mass and lactation length. Abstract : Age at primiparity (AP) is a key life history trait which is crucial to the evolution of life history strategies. This trait is particularly interesting in pinnipeds because the commonly observed trade‐off between offspring quality and quantity does not apply to this taxon as they are monotocous animals. Our comparative study on the evolution of AP in pinnipeds elucidates thus other important evolutionary correlates and shows that variation in AP is likely the result of the costs and benefits of early reproduction mediated by investment via relative birth mass and lactation length.